Phylogenomic analyses reveal a rare new genus of wasp (Hymenoptera, Ichneumonidae, Cryptinae) from the Brazilian Atlantic Forest. Issue 7 (24th July 2020) - Supeleto, Fernanda A.; Santos, Bernardo F.; Brady, Seán G.; Aguiar, Alexandre P.
Abstract : Within the ichneumonid wasp tribe Cryptini (Ichneumonidae, Cryptinae), Acrosnemus gen. nov. and its single species A . occultus sp. nov. are proposed, described, and illustrated. The phylogenetic placement of the new genus is tested using data from genomic ultraconserved elements in a matrix with 126 other species of Cryptini and five outgroup taxa. Phylogenetic analyses indicate the new genus is related to Melanocryptus Cameron, from which it can be distinguished by the presence of a conspicuous anterolateral tooth on the first metasomal tergite; tip of ventral valve of ovipositor with a dorsal lobe that partly encloses dorsal valve; posterior transverse carina represented only by two distinct sublateral crests; and female antenna with a distinct white band. The new genus presents a mosaic of morphological traits from various cryptine lineages, highlighting the ubiquitous morphological homoplasy among cryptines. The single species is recorded only from one Atlantic Forest fragment in south-eastern Brazil. Sampling history suggests it is naturally rare. http://www.zoobank.org:pub:F2519AD0-9150-4207-9F17-74E72DDC4C6